2015
DOI: 10.1155/2015/893485
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Collagens in the Skin of Horses Treated with Leukocyte-Poor Platelet-Rich Plasma

Abstract: This study evaluated the immunohistochemical expression of type I (COL I) and III (COL III) collagens during the healing process of skin treated with leukocyte-poor platelet-rich plasma (LP-PRP). Seven healthy gelding crossbred horses aged 16 to 17 years were used. Two rectangle-shaped wounds were created surgically in the right and left gluteal regions. Twelve hours after wound induction, 0.5 mL of the LP-PRP was administered in each edge of the wounds of one of the gluteal regions. The contralateral region w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
1
10
0
1
Order By: Relevance
“…The shorter closure time of the wound UT with PRP was also reported by Monteiro et al (2009) in injuries induced on the dorsolateral surface of the metacarpal. However, a faster macroscopic healing may not result in better quality tissue (SOUZA et al, 2015). This was also observed in the present study, wherein the T wounds with LP-PRP demonstrated a superior feature of the scar tissue in the sixth biopsy, primarily with respect to the alignment of collagen fibers and fibroblasts, concluded after the assessment of the three evaluators.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The shorter closure time of the wound UT with PRP was also reported by Monteiro et al (2009) in injuries induced on the dorsolateral surface of the metacarpal. However, a faster macroscopic healing may not result in better quality tissue (SOUZA et al, 2015). This was also observed in the present study, wherein the T wounds with LP-PRP demonstrated a superior feature of the scar tissue in the sixth biopsy, primarily with respect to the alignment of collagen fibers and fibroblasts, concluded after the assessment of the three evaluators.…”
Section: Discussionsupporting
confidence: 75%
“…Daily measurements of the retraction on the edge of wound C were also performed, which were then scanned, and the cross-sectional area (cm 2 ) was determined using QUANT v 1.0.0.28 software (VALE et al, 2003), as previously described (SOUZA et al, 2015). Finally, before and weekly after the wound induction, hematological (hemoglobin, hematocrit, erythrocyte, total platelets, and leukocytes) and biochemical (plasma total protein and fibrinogen) characteristics were evaluated in whole blood obtained by jugular venipuncture in vacuum tubes containing EDTA as the anticoagulant.…”
Section: This Work Was Approved By the Ethics Committee Of Animal Usementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the healing time, there was no statistical difference between the study groups. Two studies showed not statistical negative ES [ 47 , 53 ]; two studies showed positive ES [ 48 , 50 ] among which one with significative statistical difference [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…O mesmo foi relatado 21 dias após lesão traumática em TCC 6 . Estudos recentemente publicados em outra espécie (equina) e em outro tecido (pele) demonstraram que, dependendo da fase do processo de regeneração ou cicatrização, a expressão de colágenos determinada mediante as técnicas como histomorfometria 53 , RT-qPCR 54 e imunoistoquímica 55 , pode não se mostrar diferença entre grupos tratados e não tratados, inclusive utilizando uma terapia regenerativa como o plasma rico em plaquetas. O mesmo pode acontecer com a laserterapia e em ratos.…”
Section: Discussionunclassified